A combined model for PV system lifetime energy prediction and annual energy assessment. (1st May 2019) - Georgitsioti, Tatiani; Pearsall, Nicola; Forbes, Ian; Pillai, Gobind
Highlights: Model development on the lifetime energy prediction and annual energy assessment. Expression of domestic PV generation potential in various climatic conditions. Demonstration of the importance of the reliability and maintenance of PV systems. Demonstration of the energy prediction risks regarding PV systems' economic viability. Abstract: This paper presents a generic model for the prediction of the lifetime energy production of photovoltaic (PV) systems and the assessment of their annual energy yield in different time periods of operation. As case studies, it considers domestic PV system generation potentials in the UK and India to demonstrate the model results across a range of contrasting climatic and operating conditions. The model combines long-term averages of solar data, a commercial PV system simulation package and a probability density function to express the range of the annual energy prediction in different time periods of system operation. Moreover, a sensitivity analysis based on degradation rates and energy output uncertainties is embedded in the lifetime energy calculations. The importance of the reliability and maintenance of the PV systems and the energy prediction risks, especially regarding economic viability, are demonstrated through the PV lifetime energy potentials in these two countries. It is shown that, even for countries that are significantly different in respect to their solar resource, PV systems may produce similar amounts of energy during their lifetime for reasonable assumptions of degradation rates and uncertainty levels.